PEMANFAATAN INFORMASI BAHAYA PETIR SEBAGAI FUNGSI PROTEKSI SUMBER DAYA NASIONAL - Sandi, Andi Windra; Admiral Musa Julius; I Dewa Ketut Kerta Widana; Maryanti; Andi Ahmad Aminullah (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Meteorologi Klimatologi dan Geofisika, 2019)
Indonesia is a tropical country and an archipelago that has two seasons namely dry and rainy. In the rainy season often a lightning phenomenon that can endanger national resources. This condition needs to be minimized by the presence of lightning hazard information. This study aims to determine the lightning hazard information display. Service lightning BMKG information in this article shows that at certain times the lightning spread very evenly in the region of South Sumatra and Java. Service lightning hazard information is very useful to support the protection functions of national resources.